The Role of the Saxophone Instrument in the Development of Music Presentation at Wedding Events in Medan City - Erwin Purba; Junaidi Purba (Formosa Journal of Multidisciplinary Research, 2023)
This article aims to determine the role of the saxophone instrument in the development of music at weddings in the city of Medan. This article uses a qualitative descriptive research method because in this research the data produced is descriptive data obtained from data in the form of writing, audio recordings, video recordings and trusted informant sources. The data collection techniques used were observation, interviews and documentation. This article also explains the role of the saxophone instrument in the development of musical presentation at weddings in the city of Medan, namely that the saxophone not only functions as a melodic function but also functions as an aesthetic function to add a majestic impression to the presentation of music.